Extrapyramidal features in advanced Down's syndrome: clinical evaluation and family history. Issue 1 (January 1991) - Vieregge, P; Ziemens, G; Freudenberg, M; Piosinski, A; Muysers, A; Schulze, B
Abstract : Extrapyramidal, frontal release, and other neurological signs were studied in 54 demented and non-demented patients with Down's syndrome (DS). Fourteen patients were demented and five showed extrapyramidal signs, mainly of the rigid-hypokinetic spectrum and similar to Parkinsonian features in advanced Alzheimer's disease (AD). None of the non-demented patients had Parkinsonian signs. The mean age of the demented DS patients with extrapyramidal signs was significantly higher than that of the patients without. Frontal release signs were present in demented and non-demented patients. A questionnaire showed no increase in either the proportion of early- or senile-onset dementia or Parkinsonism among first- and second-degree relatives of DS patients. Parkinsonian signs appear to be present at a lower frequency in DS than in advanced AD. A speculative hypothesis about a gene dosage effect of Cu/Zn-superoxide dismutase in preventing toxic radical formation in the substantia nigra of DS patients is presented.